The pollutants monitoring in the industrial wastewaters–a case study conducted in Resiţa municipality, Caraş Severin county, Romania - Alexa, Vasile; Kiss, Imre (TÁJÖKOLÓGIAI LAPOK, 2014)
Currently, the big companies should be concerned with achieving environmental performance by controlling the environmental impact of the work they carry out. These concerns fall within the context of developing economic and legislative policies, measures to encourage the environmental protection, increasing concerns of interested parties in the environmental issues and sustainable development. Integrated environmental authorization is issued by the competent authority in order to ensure a high level of protection for the environment as a whole, subject to regulations on the quality of air, water and soil. The monitoring plan must include the monitoring of emissions and imissions in air, the monitoring of emissions in water, the monitoring of the soils qualities and the monitoring of the groundwaters. In this paper, the results of monitoring the particulate matter emissions, sediment particulate emissions and immission level are presented, based on a case study conducted on the administrative territory of Resiţa municipality, Caraş Severin county (Romania). Based on the results of monitoring the production activities, in order to reduce the pollutant emission and immission levels, some conclusions and remarks are presented. We have analyzed the quantities of metallic elements (Mn, Ni, Zn, Cr, Cu and Pb) found in the wastewater from the areas of steel works and rolling mills, and we performed a calculation of pollutants in water, based on the measurements made, between 2008–2012, in accordance with the Romanian standards and legislative requirements.